The Preparation of Cu-Modified Cryptomelane Type-Manganese Oxide Catalysts by one Step sol-gel Synthesis for Decomposition of Methylene Blue. (November 2019) - Awaluddin, A; Janah, SR; Anggraini, R; Siregar, SS
Abstract: The cryptomelane manganese oxide octahedral molecular sieve (OMS-2) and Cu-modified cryptomelane octahedral molecular sieve (Cu-OMS-2) with different Cu concentrations (1, 5, 10%) were successfully prepared by one-step sol-gel synthesis. The XRD patterns of OMS-2 and Cu-OMS-2 remain unchanged, indicating the Cu ions are well incorporated within OMS-2, except the peak due to (101) plane appears and grows significantly until 5% Cu incorporation. The SEM images revealed that the additions of Cu ions in the OMS-2 have a remarkable impact on the Cu-OMS-2 morphologies, especially for 10% Cu incorporation. The bulk analysis by AAS showed the steady decreases in K + and Mn concentrations, and increase in Cu concentrations, suggesting that some Cu 2+ ions are replacing K + in the tunnel and Mn in the framework of OMS-2. The catalytic tests for the degradation methylene blue (MB) by heterogeneous Fenton processes revealed that the catalytic performance of Cu-OMS-2 increases remarkably with the increased concentrations of Cu doping. The increased catalytic activities for Cu-OMS-2 are associated with the smaller particles sizes are revealed by SEM results.